Hubungan Ketepatan Terminologi Medis dengan Keakuratan Kode Diagnosa Penyakit Sistem Respirasi di Rumah Sakit - Hotmarina Lumban Gaol; Nasipta Ginting; Jev Boris; Flower Desma Sihaloho; Kajol Santa Monika (Yayasan Literasi Sains Indonesia, 2026)
Accuracy in the provision of diagnosis codes is something that must be considered by medical record personnel, the accuracy of diagnosis codes is very important in the field of clinical data management, cost billing, along with matters related to health services. Factors causing inaccuracies in diagnosis codes are the use of diagnosis abbreviations, and writing diagnoses that do not use medical terminology terms. The purpose of the study is to analyze the relationship between the accuracy of medical terminology and the accuracy of diagnosis codes for respiratory system diseases. The type of research design used in this study is an analytic research design with a cross sectional approach. The sample in this study is patient medical resume data, totaling 72 samples. The instrument used in the study is a checklist sheet. Data analysis using the chi-square statistical test. The results of the chi-square statistical test obtain a p-value of 0.000 (p <0.05) so it is concluded that there is a significant relationship between the accuracy of medical terminology and the accuracy of the diagnosis code of respiratory system diseases. It is hoped that the results of this study can be used by hospitals to encourage and provide ongoing training to doctors and other health workers regarding the importance of complete, clear medical record documentation, and using standardized and consistent medical terminology.